Hegel and contemporary practical philosophy: beyond Kantian constructivism - Gledhill, James; Stein, Sebastian (Routledge, Taylor & Francis Group, 2020)
IntroductionJames Gledhill and Sebastian SteinPart 1: Hegelian Ethics Between Constructivism and Realism1. Hegel's "Actualist" Idealism and the Modality of Practical Reason Paul Redding2. Choosing to do the Right Thing: Aristotle, Kant and Hegel on Practical Normativity and the Realism-constructivism Debate Sebastian Stein3. Constraint and the Ethical Agent: Hegel Between Constructivism and RealismJoshua Wretzel4. Hegel's Meta-Ethical Non-ConstructivismSebastian Ostritsch5. Rawls's Post-Kantian ConstructivismJames GledhillPart 2: Hegelian Political Normativity Between Reason and History6. Hegel's Political Philosophy as Constructivism of the RealAngelica Nuzzo7. Kant, Hegel and our Fate as Zoôn PolitikonKenneth R. Westphal8. Finding by Making: The Mediating Role of Social Constructions, Commitments, and Resonance in Hegelian Normative RealismArto Laitinen9. Historical ConstructivismChristopher Yeomans10. Critical Agency in Hegelian Ethics: Social Metaphysics versus Moral ConstructivismMichael J. Thompson11. Hegel on a Form of Collective IrrationalityRobert PippinPart 3: Hegelian Perspectives on Contemporary Politics12. Saving Multiculturalism with Stakeholding: Hegel and the Challenges of PluralismThom Brooks13. Hegelian Sittlichkeit, Deweyan Democracy, and Honnethian Relational Institutions: Beyond Kantian Practical PhilosophyPaul Giladi14. Hegel and the Intercultural Conception of Universal Human RightsAndrew Buchwalter
Keywords: Kant, Immanuel -- 1724-1804; Hegel, Georg Wilhelm Friedrich -- 1770-1831; Electronic books; Aufsatzsammlung; Konstruktivismus; Kantianismus; Ethik; Praktische Philosophie; Hegel, Georg Wilhelm Friedrich